Vortex core reversal by elastic waves in ferromagnetic materials. (15th December 2021) - Sun, Jiajun; Zhang, Yong; Wang, Jie
Abstract: Magnetic vortex has attracted increasing attention due to its potential application in magnetic logic and memory devices. With the development of straintronics, acoustic waves could remotely control the topologically nontrivial magnetic bits such as magnetic vortices. Understanding the dynamic response of magnetic vortex subjected to elastic waves is crucial for the future logic and memory devices. In the present work, a dynamic phase field model is developed to investigate the dynamic magnetoelastic coupling behavior between elastic waves and magnetic vortices. Phase field simulations show that the magnetic vortex core can flip over under the elastic waves with gigahertz frequency. Compared with the results of conventional phase field model without the elastodynamic term, it is found that the strain gradient caused by elastic wave plays an important role in the reversal of vortex core. When the strain gradient in the ferromagnetic material reaches a certain value, the vortex core is likely to flip over. The elastic waves with larger magnitudes and frequencies have the larger strain gradient, which are more easily to cause the reversal of vortex core. In addition to the strain gradient, magnetic damping constant also has great influence on the vortex core reversal by changing the precession process of magnetization. Larger magnetic damping constant makes the smaller precession of magnetization, which retards the reversal of vortex core. The results of this study suggest a mechanical way for the remote control of magnetic vortices by elastic waves.